2011
DOI: 10.1016/j.anbehav.2010.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Queen acceptance in a socially polymorphic ant

Abstract: A central question in social evolution is what processes regulate the number of breeders in each social group. Here, we tested whether differences in the rate of acceptance of new queens by resident workers could be a proximate cause explaining the coexistence of single-and multiple-queen colonies in an ant population. We found that Formica selysi workers discriminated against foreign (non-nestmate) queens, which contributes to maintaining the genetic integrity of the social group essential to kin selection. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…A degree of lability in social structure is consistent with previous experiments that showed that F. selysi queens from both social forms can establish colonies either independently or in associations (Reber et al 2010) and that colonies of both social forms tend to reject unrelated queens, but will often accept nestmate queens (Meunier et al 2011). However, cross‐fostering experiments revealed that size differences between monogynous and polygynous queens, as well as the development time and growth rate of worker brood, matched their social origin, rather than their fostered environment (Meunier and Chapuisat 2009; Purcell and Chapuisat 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A degree of lability in social structure is consistent with previous experiments that showed that F. selysi queens from both social forms can establish colonies either independently or in associations (Reber et al 2010) and that colonies of both social forms tend to reject unrelated queens, but will often accept nestmate queens (Meunier et al 2011). However, cross‐fostering experiments revealed that size differences between monogynous and polygynous queens, as well as the development time and growth rate of worker brood, matched their social origin, rather than their fostered environment (Meunier and Chapuisat 2009; Purcell and Chapuisat 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our results highlight the great diversity of reproductive strategies exhibited by social insects (Heinze and Keller 2000). In particular, joining unrelated colonies or taking over queenless nests appear to be viable options for young queens, in addition to staying in the maternal nest (Meunier et al 2011) or founding a new colony independently (Reber et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These overall patterns are probably consistent across socially polymorphic ant species, because social structure variation is generally associated with similar life history changes and morphological variation in queens and workers (Bourke & Franks, ; Heinze & Keller, ; Schwander et al ., and references herein). However, we do not yet have direct evidence that the social forms of F. selysi differ in their dispersal and colony founding strategies (Reber et al ., ; Meunier et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, both types of workers were more aggressive towards introduced foreign workers from the alternative rather than identical social form, 11 and monogyne workers were significantly more aggressive towards foreign queens of monogyne than polygyne origin. 12 The influence of queen number on the chemical signatures of workers has also been reported in two other ant species. In Messor barbatus, 13 where the social origin of introduced workers influences their acceptance in monogyne colonies, 14 and in the fire ant Solenopsis invicta, 15 where nestmate discrimination depends on the alleles of the gene Gp-9 present in the individuals and in the recipient colony.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%